Ionospheric Nighttime F‐Region Irregularities During Geomagnetically Quiet Conditions as Observed With 205 MHz VHF Radar at an Equatorial Trough Station, Cochin. Issue 6 (26th May 2022) - Varadarajan, Rakesh; Haridas, Sreekumar; Manoj, M. G.; Rebello, Rejoy; Paul, Binu; Unnikrishnan, K.; Sukumarapillai, Abhilash; Mohanakumar, K.
Abstract: The VHF radar operating at 205 MHz frequency installed at the Cochin University of Science and Technology (CUSAT) has been configured to probe the nighttime ionospheric field‐aligned irregularities (FAIs) over the near‐equatorial site at Cochin, India during the solar minimum periods. Even though the study period includes the minimum of the 24th and 25th solar cycles, a total of 40 nighttime irregularity events were observed at F‐region heights (150–500 km). Bottom‐type and bottom‐side irregularities were observed in this period, but no large‐scale topside ones at F‐region heights. The nighttime irregularities were most commonly observed at average heights of 200–250 km, accounting for 50% of the total events, and 27.5% of the irregularities preferentially occurred after sunset between 19 and 20 LT. While long‐duration irregularity events were not prominent during this period, irregularities that lasted for less than 50 min were predominant. To check the capability of the 205 MHz VHF radar in observing FAIs, the radar observations were compared with the European Space Agency's ionospheric observation data from the Swarm B satellite. Several derived parameters from the Swarm data set such as electron density ( N e ), background N e (b N e ), electron temperature ( T e ), rate of electron density (ROD), index of ROD (RODI), median vertical total electron content (mVTEC), absolute VTEC (aVTEC), rate of TEC (ROT), ROTI, Bubble Index, and Bubble Probability were utilized for characterizing the ionospheric irregularities. The observation from the Swarm B satellite agrees well with that obtained from the VHF radar. Plain Language Summary: This study presents the statistical analysis of the ionospheric (F‐region) plasma irregularities observed over a near‐equatorial site Cochin, India during 2020–2021. The recently installed 205 MHz VHF radar at the Cochin University of Science and Technology (CUSAT) has been configured suitably to investigate the ionospheric effects. It is observed that the nighttime irregularities were most commonly observed at average heights of 200–250 km, accounting for 50% of the total events and 27.5% of the irregularities preferentially occurred during the post‐sunset period of 19–20 LT. The simultaneous observation of the Swarm B satellite agrees well with that obtained from the VHF radar proving the potential of the radar in probing the ionosphere. Apart from Rayleigh‐Taylor instability, a major factor contributing to the upwelling plumes is the convergence of equatorward meridional wind streams that can raise the F layer height. Key Points: Characteristics of nighttime FAIs over near‐equatorial site using 205 MHz VHF radar Bottom‐type or bottom‐side instability observed in nighttime F‐region heights Concurrent observation by Swarm Bravo Satellite confirms the findings